• Matéria: Matemática
  • Autor: jjv2002666
  • Perguntado 8 anos atrás

Determine a função afim sabendo que f(- 3)=25 e f(2) = - 5.
( )f(x) = 4x - 6.
( )f(x) = - 6x + 7.
( )f(x) = - 3x + 2.
( )f(x) = 5x + 17.

Respostas

respondido por: smitearena1
1

Letra b f(x)= -6x+7       Substituindo -3                                             f(x)= -6.(-3)+7                                                      f(x)= 18+7                                                      f (x)=25                Substituindo 2 f(x)= -6.(2)+7 f(x)= -12+7 f(x)= -5

Perguntas similares